Study of typhoon-induced storm surge along Manila Bay based on SLOSH modeling - Villacrusis, Jan Reuel D.
The Philippine Port Authority (PPA) has been using port freeboard design in the Philippines that is based on the American design codes which is currently MLLW + 3m. There is no study done to justify its use for Philippine ports. This study aims to be able to illustrate for Manila Bay the magnitude of surge height that storms can generate and change or reinforce the freeboard design regulations for the safety of citizens and structure. By using SLOSH modeling, this study generates a basin model of Manila Bay and performs numerical modeling of storm-induced storm surges. The simulations also synthesize the maximum envelope of water due to several storms, which are taken as the maximum surge heights along the Bay. The resulting value for the maximum surge height along Manila Bay assuming a tidal datum of 1.28 m from the mean sea level has been determined to be 2.62 m to 2.65 m. The values generated mostly came from storm Rosing since its strength far outstrips the other storms but storm Frank generated similar results while being a relatively weaker storm due to the trajectory it took across the Philippines. Storm Frank generated surge heights of 2.35 m to 2.53 m along Manila Bay. The distance of the mean sea level from the mean lower low water (MLLW) is then added to reflect the vertical siting requirements of port design in the Philippines (-0.49 m). Based on the results, the recommended vertical siting is 3.14 m for the Manila Bay coastline.